Endovascular Treatment for Vascular Injuries of the Extremities - Tae Won Choi; Yohan Kwon; Jinoo Kim; Je Hwan Won (Journal of the Korean Society of Radiology, 2023)
Vascular injuries of the extremities are associated with a high mortality rate. Conventionally, open surgery is the treatment of choice for peripheral vascular injuries. However, rapid development of devices and techniques in recent years has significantly increased the utilization and clinical application of endovascular treatment. Endovascular options for peripheral vascular injuries include stent-graft placement and embolization. The surgical approach is difficult in cases of axillo-subclavian or iliac artery injuries, and stent-graft placement is a widely accepted alternative to open surgery. Embolization can be considered for arterial injuries associated with active bleeding, pseudoaneurysms, and arteriovenous fistula and in patients in whom embolization can be safely performed without a risk of ischemic complications in the extremities. Endovascular treatment is a minimally invasive procedure and is useful as a simultaneous diagnostic and therapeutic approach, which serve as advantages of this technique that is widely utilized for vascular injuries of the extremities.